Learning for adolescents with dyslexia exploring strategies, challenges, and motivations - Palmares, Rey Alexander V (University of the Philippines Visayas, 2017)
Dyslexia is a relatively difficult learning disability to understand due to the varied degrees that each learner uniquely experiences. It is difficult to diagnose because of the commonality of its symptoms. Such a difficulty means that dyslexia is often overlooked, leading to scarce development in learning or teaching techniques specific to dyslexics. Therefore, learners with dyslexia are mostly left to their own devices, suffering deep emotional wounds brought on by a misunderstanding environment. Through Rieskamp and Otto's Strategy Selection Learning Theory (2006), this study delves into the thought processes of five adolescents with dyslexia. Through an interview, the study probed into their daily challenges, motivations for finishing school, and strategies employed to overcome their learning difficulties. Responses were sorted into two overarching themes : the learning process and reflection of "self". These themes refer to the fators that contribute to the selection of a learning strategy. Results reveal that most learners purposively employ strategies which prioritize the avoidance of challenges to the self (i.e. bullying, self-depreciation) and the accruement of self-confidence through feedback from sources of motivation (i.e. commendation from parents, friends, and teachers following success) over the achievement of a particular learning goal. While the strategies vary from one learner to the other, the justifications for the selection of such particular strategies revolve around overcoming perceived weaknesses and building on perceived strengths.